Randomized factorial trial of esomeprazole and aspirin in Barrett’s oesophagus: the Aspirin and Esomeprazole Chemoprevention in Barrett’s metaplasia Trial (AspECT) - Jankowski, Janusz A.Z.; de Caestecker, John; Love, Sharon B.; Reilly, Gavin; Watson, Peter; Sanders, Scott; Ang, Yeng; Morris, Danielle; Bhandari, Pradeep; Attwood, Stephen; Ragunath, Krish; Rameh, Bashir; et al. (Elsevier, 2018)
Background: Oesophageal adenocarcinoma (OA) is the sixth commonest cause of cancer death worldwide and Barrett’s oesophagus (BO) is the most significant risk factor. We evaluated the efficacy of high-dose esomeprazole proton pump inhibitor acid suppression (PPI) and aspirin in improving outcome for BO patients in the largest such randomized controlled trial.